If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 183 + -2x = 43x + 23 Reorder the terms: 183 + -2x = 23 + 43x Solving 183 + -2x = 23 + 43x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-43x' to each side of the equation. 183 + -2x + -43x = 23 + 43x + -43x Combine like terms: -2x + -43x = -45x 183 + -45x = 23 + 43x + -43x Combine like terms: 43x + -43x = 0 183 + -45x = 23 + 0 183 + -45x = 23 Add '-183' to each side of the equation. 183 + -183 + -45x = 23 + -183 Combine like terms: 183 + -183 = 0 0 + -45x = 23 + -183 -45x = 23 + -183 Combine like terms: 23 + -183 = -160 -45x = -160 Divide each side by '-45'. x = 3.555555556 Simplifying x = 3.555555556
| 9-10x=209-45x | | 2x+3(x-5)=5(2x-3) | | 2mn+9mp= | | 4(x+3)-7x=6 | | 10-3x+8=30+2x+48 | | 17x+8=42 | | 9x-6-5x=8+x-14 | | 56-6x=3x+21 | | 5-7x=3x+21 | | -70-9x=43-21x | | (5y-2)=52 | | 14-8x+6-5x=10+2x-5 | | 6x+18=116-6x | | (x+2)(2-x)=6x-x | | 2x+36=21x-36 | | 17-6x=4x-8 | | 9-5k+2k=k-23 | | x^2+4x-1=9x-5 | | 6x+30=13-33 | | x^2+8x-2=7 | | x^2-(a+2b)x+b^2+ab=0 | | 24a=36 | | 12-x=30-4x | | 3x+4=5x-16 | | x^2+32x-196=0 | | x-17=6x+8 | | 9x-5=x+19 | | 9x+6=6x+10 | | 7x-20=04-3x | | 7(2x-5)=42 | | 21-7x=10+4x | | x+2=-3x+30 |